Mutu Simplisia dan Komposisi Kulit Pisang Barangan (M. acuminata Colla) Sebagai Bahan Dental Preventif Dengan Metode Pengeringan Berbeda - Astrid Yudhit; Sondang Pintauli; Ellyza Herda; Aminah Dalimunthe (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: The drying process in the preparation of herbal material affects the quality, chemical compound content, and mineral composition of herbal ingredients. Barangan banana peel (Musa acuminata Colla) has potential as a preventive dental agent due to its phytochemical and mineral content. Objective: This study aimed to analyze the simplicia quality (moisture content and total ash content) as well as the chemical compound and mineral composition of Barangan banana peel dried using two different methods. Methods: This was a qualitative analytical study. Cleaned and chopped Barangan banana peels were divided into two groups: oven-dried (OD; 60°C for 12 hours) and freeze-dried (FD; -65°C for 4 hours followed by 48 hours of freeze drying). The simplicia was ground using a ball mill (500 rpm for 6 hours). Moisture content was determined using the toluene method, while total ash content was measured by heating at 800°C. Identification of chemical compounds and minerals was performed using GC-MS and XRF, respectively. Results: Moisture content of the OD group was 9.23% and of the FD group was 7.11%; total ash content was 10.83% and 10.60%, respectively. Both met the standards of the Indonesian Herbal Pharmacopoeia (moisture content <10%, total ash content <15%). GC-MS identification revealed that the FD group exhibited a greater variety of chemical compounds (12 components) compared to the OD group (7 components). The highest mineral content in both groups was potassium (K), with magnesium (Mg) being higher in the OD group (15.32%) than in the FD group (9.95%). Conclusion: The drying method affects the quality and composition of Barangan banana peel. Freeze drying resulted in lower moisture content and greater phytochemical diversity, whereas oven drying tended to preserve higher mineral content for certain elements. The simplicia of Barangan banana peel from both methods has potential to be developed as a preventive dental material.